Fabrication and growth mechanism of t-selenium nanorods during laser ablation and fragmentation in organic liquids - Baimler, Ilya V.; Simakin, Alexander V.; Dikovskaya, Anastasia O.; Voronov, Valery V.; Uvarov, Oleg V.; Smirnov, Alexander A.; Sibirev, Alexey V.; Dorokhov, Alexey S.; Gudkov, Sergey V. (Frontiers in Chemistry, 2024)
Introduction The process of forming selenium nanoparticles with various shapes and structures through laser ablation and fragmentation in various solvents has been explored. Methods Laser ablation and laser fragmentation techniques were employed using nanosecond Nd:YAG second harmonic laser irradiation in 9 different working fluids, including water. The characteristics of the resulting nanoparticles were assessed using transmission electron microscopy (TEM), dynamic light scattering (DLS), spectroscopy, and X-ray diffraction (XRD) methods. Results Laser ablation and subsequent laser fragmentation of some organic solvents, such as ethanol, propanol-2, isobutanol, polyethylene glycol, and diethanolamine, have been found to produce trigonal selenium in the form of elongated nanorods approximately 1 μm long and 200 nm thick, with a well-defined crystal structure. In contrast, the use of deionized water, acetone, glycerol, and benzene as solvents results in the formation of spherical amorphous nanoparticles approximately 100 nm in diameter. Discussion The polarity of the solvent molecules has been shown to influence the growth of crystalline selenium nanorods in solution during laser ablation and laser fragmentation. Generally, polar solvents hinder the growth of crystalline nanorods, due to interactions between selenium and solvent molecules. Nonpolar solvents, on the other hand, allow for laser fragmentation to reduce particle size and initiate the epitaxial growth of elongated, crystalline selenium nanorods.